HUBUNGAN PERCAYA DIRI DAN KOORDINASI MATA-TANGAN DENGAN KEMAMPUAN SERVIS ATAS OLAHRAGA BOLA VOLI DI SMK PAMOR CIKAMPEK - Komarudin Agung Suhara; Irfan zinat achmad; Akhmad Dimyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between self-confidence and hand-eye coordination with the overhand service ability in volleyball among students of SMK Pamor Cikampek. The overhand service skill is one of the fundamental techniques that plays an important role in initiating attacks and determining the direction of the game. Mastery of this technique is not only influenced by physical ability but also by psychological factors such as self-confidence and motor abilities such as hand-eye coordination. This research employed a correlational method with a quantitative approach. The population consisted of all volleyball extracurricular participants at SMK Pamor Cikampek, totaling 30 students. The sampling technique used was total sampling, meaning that all members of the population were included as research samples. The instruments used consisted of a self-confidence questionnaire to measure psychological aspects, a tennis ball throw-catch test to assess hand-eye coordination, and an overhand service test to measure basic technical ability. The data were analyzed using the Pearson Product Moment correlation test with a significance level of 0.05. The results showed a correlation coefficient value of 0.217, which falls into the weak category. This means that there is a positive relationship between self-confidence and hand-eye coordination with overhand service ability, although the contribution is relatively small. These findings suggest that although both factors play a role in improving overhand service performance, other factors such as regular training, playing experience, and physical condition also influence students’ service skills.